PENINGKATAN MINAT BELAJAR SISWA MELALUI PENGEMBANGAN E-MODUL PADA PELAJARAN KBGT (Kerja Bengkel dan Gambar Teknik) PADA ERA NEW NORMAL DI SMKN 8 MALANG - Afan Alfarozi; Ulfa Rahayu Saputra; Ahmad Syaifudin; Tuwoso Tuwoso (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
The pandemic makes learning in the school environment limited, as a result the ability of students to understand and master the material of a subject decreases. Distance learning / online is the main choice so that the learning process continues. Online learning results in limited students getting learning resources from textbooks, so that their interest in reading and learning decreases. Researchers make innovations to overcome these problems by making an e-module product as student learning material with concepts and material content that are more interesting and easily understood by students. It is hoped that this e-module can increase students' interest in learning in KBGT lessons (workshop work and technical drawing) at SMKN 8 Malang. This study uses the Borg and Gall version of the R&D (Research & Development) method which is simplified by Anik Ghufron. The development model used has four stages, namely preliminary studies, development, field testing, and product development dissemination. This research is based on interviews and validation questionnaires. The results showed that the KBGT e-module developed was declared very feasible with a material validity value of 3.35 and media value of 3.43.